Potential use of supervised injection services among people who inject drugs in a remote and mid-size Canadian setting - Sanjana Mitra; Beth Rachlis; Bonnie Krysowaty; Zack Marshall; Cynthia Olsen; Sean Rourke; Thomas Kerr (BMC, 2019)
Abstract Background While supervised injection services (SIS) feasibility research has been conducted in large urban centres across North America, it is unknown whether these services are acceptable among people who inject drugs (PWID) in remote, mid-size cities. We assessed willingness to use SIS and expected frequency of SIS use among PWID in Thunder Bay, a community in Northwestern, Ontario, Canada, serving people from suburban, rural and remote areas of the region. Methods Between June and October 2016, peer research associates administered surveys to PWID. Sociodemographic characteristics, drug use and behavioural patterns associated with willingness to use SIS and expected frequency of SIS use were estimated using bivariable and multivariable logistic regression models. Design preferences and amenities identified as important to provide alongside SIS were assessed descriptively. Results Among 200 PWID (median age, IQR: 35, 28-43; 43% female), 137 (69%) reported willingness to use SIS. In multivariable analyses, public injecting was positively associated with willingness to use (Adjusted Odds Ratio (AOR): 4.15; 95% confidence interval (CI): 2.08-8.29). Among those willing to use SIS, 87 (64%) said they would always/usually use SIS, while 48 (36%) said they would sometime/occasionally use SIS. In multivariable analyses, being female (AOR: 2.44; 95% CI: 1.06-5.65) and reporting injecting alone was positively associated with higher expected frequency of use (AOR: 2.59; 95% CI: 1.02-6.58). Conclusions Our findings suggest that SIS could play a role in addressing the harms of injection drug use in remote and mid-sized settings particularly for those who inject in public, as well as women and those who inject alone, who report higher expected frequency of SIS use. Design preferences of local PWID, in addition to differences according to gender should be taken into consideration to maximize the uptake of SIS, alongside existing health and social service provisions available to PWID.